The Influence of Plasma Albumin Concentration on the Analysis Methodology of Free Valproic Acid by Ultrafiltration and Its Application to Therapeutic Drug Monitoring - Zhang, Zhi-Qing; Dong, Wei-Chong; Yang, Xiu-Ling; Zhang, Jin-Feng; Jiang, Xin-Hui; Jing, Shao-Jun; Yang, Hong-le; Jiang, Ye (Therapeutic drug monitoring, 2015)
Free drug analysis is increasingly becoming popular in therapeutic drug monitoring (TDM). Centrifugal ultrafiltration (CF-UF) is the primary method to separate free drug from that of bound drug. However, the volume ratio of ultrafiltrate to sample solution (Vu/Vs) affects the accuracy of CF-UF, which highly depends on the different plasma conditions. Plasma protein concentrations in patients are different from those observed in healthy subjects, and there are also significant differences among patients with different diseases. Only very few studies have reported on the effect of protein concentration on the analysis methodology of free drug by CF-UF. In this study, valproic acid was used as the representative drug, and plasma samples with different albumin concentrations were analyzed by CF-UF and hollow fiber centrifugal ultrafiltration (HFCF-UF). There was no significant difference of free drug concentrations by HFCF-UF and CF-UF when plasma albumin concentrations ranged 40-60 g/L. However, at low albumin concentrations (<40 g/L), a considerable difference was detected, and the difference was increased with the decrease of plasma albumin concentration. When the albumin concentration was as low as 10 g/L, the free drug concentration was 17.3 mcg/mL by CF-UF, whereas it was 10.2 mcg/mL by HFCF-UF. The accuracy of free drug measurement by CF-UF was albumin concentration dependent. However, such an effect was not observed when samples were prepared by HFCF-UF, which was more suitable for TDM of plasma samples from different patients. Therefore, this method could be readily applied to the measurement of free valproic acid plasma concentrations for TDM in patients.